[8]Cyclo‐para‐phenylmethine as a Super‐Cyclooctatetraene: Dynamic Behavior, Global Aromaticity, and Open‐Shell Diradical Character in the Neutral and Dicationic States. Issue 43 (14th September 2022) - Li, Zhengtao; Hou, Xudong; Han, Yi; Fan, Wei; Ni, Yong; Zhou, Qifeng; Zhu, Jun; Wu, Shaofei; Huang, Kuo‐Wei; Wu, Jishan
Abstract: An [8]cyclo‐ para ‐phenylmethine derivative ([8]CPPM‐Mes ) was synthesized. X‐ray analysis revealed a tub‐shaped geometry similar to the cyclooctatetraene, with alternating benzenoid/quinoid structure. Variable‐temperature NMR measurements disclosed a slow valence tautomerization process with an interconversion energy barrier of about 11.7 kcal mol −1 at coalescence temperature (273 K), and two more lower‐barrier dynamic processes involving flipping of the 1, 4‐phenyl rings on the backbone and rotation of the mesityl substituents. Its dication ([8]CPPM‐Mes 2+ ) adopts a bowl‐like geometry with a smaller depth of the cavity, and a slow bowl inversion process was observed by dynamic NMR. The bond lengths of the benzenoid/quinoid rings are more averaged via electron delocalization and the molecule shows global aromaticity, which was further validated by NMR and theoretical analysis. [8]CPPM‐Mes 2+ exhibits open‐shell diradical character with a small singlet‐triplet energy gap (−1.8 kcal mol −1 ). Abstract : A super‐cyclooctatetraene, one new core‐expanded analogue of cyclooctatetraene, has been synthesized by insertion of a benzenoid/quinoid C6 H4 unit into each C−C bond. The neutral molecule shows three dynamic processes on the NMR time scale and non‐aromatic character, whereas its dication exhibits enhanced planarity, global aromatic, and open‐shell diradical character.